Review Literatur Implementasi Material Flow Cost Accounting dalam Peningkatan Efisiensi Sumber Daya dan Pengendalian Biaya Lingkungan - Nola Rahma Diny; Kenya Adeliani (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to explore the application of Material Flow Cost Accounting (MFCA) as an environmental accounting approach to improve resource efficiency and control environmental costs. The analysis was conducted using a Systematic Literature Review (SLR) method based on 30 scientific articles published between 2020 and 2025, collected from both national dan international databases. The results show that MFCA assists organizations in identifying material waste, reducing hidden costs, and improving the efficiency of raw material and energy use by approximately 35%. Furthermore, the adoption of MFCA supports sustainability reporting in line with ISO 14051 and ISO 14053 standards and contributes to achieving the Sustainable Development Goals (SDGs) while enhancing corporate value. Although its implementation in developing countries such as Indonesia still encounters several technical and policy barriers. MFCA has proven effective as a strategic environmental accounting tool that aligns economic efficiency with environmental sustainability.